A New Drug-Free Life: The essence of professional's presence in drug survivor's family - Yeyentimalla, Yeyentimalla; Suryawati, Sri (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2022)
The story begins at the Galilee Foundation Drug Rehabilitation Center in Palangka Raya City in July 2018. We are a team that provides professional assistance to drug survivors at the Panti (in Indonesia, rehabilitation homes for drugs users are termed Panti). One of the four-drug survivors enrolled in our study was Jeremy, 19 years old. We were helping Jeremy to reconnect with his family. This activity was a part of the social reintegration activity of the drug rehabilitation program.